Confusion about currying and point free style in Haskell - haskell

I was trying to implement the function
every :: (a -> IO Bool) -> [a] -> IO Bool
which was the topic for this question. I tried to do this without explicit recursion. I came up with the following code
every f xs = liftM (all id) $ sequence $ map f xs
My function didn't work since it wasn't lazy (which was required in the question), so no upvotes there :-).
However, I did not stop there. I tried to make the function point-free so that it would be shorter (and perhaps even cooler). Since the arguments f and xs are the last ones in the expression I just dropped them:
every = liftM (all id) $ sequence $ map
But this did not work as expected, in fact it didn't work at all:
[1 of 1] Compiling Main ( stk.hs, interpreted )
stk.hs:53:42:
Couldn't match expected type `[m a]'
against inferred type `(a1 -> b) -> [a1] -> [b]'
In the second argument of `($)', namely `map'
In the second argument of `($)', namely `sequence $ map'
In the expression: liftM (all id) $ sequence $ map
Failed, modules loaded: none.
Why is that? I was under the impression that it was possible to simply drop trailing function arguments, which basically is what currying is about.

The definition of $ is
f $ x = f x
Let's fully parenthesize your function:
every f xs = (liftM (all id)) (sequence ((map f) xs))
and your curried version:
every = (liftM (all id)) (sequence map)
As you noticed, these are not identical. You can only drop trailing function arguments when they are the last thing applied. For example,
f x = g c x
is actually
f x = (g c) x
and the application of (g c) to x comes last, so you can write
f = g c
One pattern with the application operator $ is that it often becomes the composition operator . in points-free versions. This is because
f $ g $ x
is equivalent to
(f . g) $ x
For example,
every f xs = liftM (all id) $ sequence $ map f xs
can become
every f xs = (liftM (all id) . sequence . map f) xs
at which point you can drop xs:
every f = liftM (all id) . sequence . map f
Eliminating the argument f is more difficult, because it is applied before the composition operator. Let's use the definition of dot from http://www.haskell.org/haskellwiki/Pointfree:
dot = ((.) . (.))
With points, this is
(f `dot` g) x = f . g x
and is exactly what we need to make every fully points-free:
every = (liftM (all id) . sequence) `dot` map
Sadly, due to restrictions in the Haskell type system, this one needs an explicit type signature:
every :: (Monad m) => (a -> m Bool) -> [a] -> m Bool

Related

Filter a list of tuples by fst

What I'm trying to do is not really solve a problem, but more to learn how to write Haskell code that composes/utilizes basic functions to do it.
I have a function that takes a list of tuples (String, Int) and a String, and returns a tuple whose fst matches the given String.
This was fairly easy to do with filter and lambda, but what I want to do now, is remove the rightmost argument, ie. I want to refactor the function to be a composition of partially applied functions that'll do the same functionality.
Original code was:
getstat :: Player -> String -> Stat
getstat p n = head $ filter (\(n', v) -> n' == n) $ stats p
New code is:
getstat :: Player -> String -> Stat
getstat p = head . (flip filter $ stats p) . cmpfst
where cmpfst = (==) . fst . (flip (,)) 0 -- Wrong :-\
The idea is to flip the filter and partially apply by giving in the list of tuples (stats p) and then compose cmpfst.
cmpfst should be String -> (String, Int) -> Bool so that when String argument is applied, it becomes a -> Bool which is good for the filter to pass in tuples, but as you can see - I have problems composing (==) so that only fst's of given tuples are compared.
P.S. I know that the first code is likely cleaner; the point of this task was not to write clean code but to learn how to solve the problem through composition.
Edit:
I understand well that asking for a head on an possibly empty list is a bad programming that'll result in a crash. Like one earlier poster mentioned, it is very simply and elegantly resolved with Maybe monad - a task I've done before and am familiar with.
What I'd like the focus to be on, is how to make cmpfst composed primarily of basic functions.
So far, the furthest I got is this:
getstat :: Player -> String -> Stat
getstat p = head . (flip filter $ stats p) . (\n' -> (==(fst n')) . fst) . (flip (,)) 0
I can't get rid of the (a -> Bool) lambda by composing and partially applying around (==). This signals, to me, that I either don't understand what I'm doing, or it's impossible using (==) operator in the way I imagined.
Furthermore, unless there's no exact solution, I'll accept signature-change solution as correct one. I'd like not to change the signature of the function simply because its a mental exercise for me, not a production code.
If I were writing this function, I'd probably have given it this type signature:
getstat :: String -> Player -> Stat
This makes it easy to eta-reduce the definition to
getstat n = head . filter ((== n) . fst) . stats
In a comment, you reached
getstat p = head . (flip filter $ stats p) . (\n (n', v) -> n' == n)
I wonder if there's a nicer composition that can eliminate the anon f.
Well, here it is
\n (n', v) -> n' == n
-- for convenience, we flip the ==
\n (n', v) -> n == n'
-- prefix notation
\n (n', v) -> (==) n n'
-- let's remove pattern matching over (n', v)
\n (n', v) -> (==) n $ fst (n', v)
\n x -> (==) n $ fst x
-- composition, eta
\n -> (==) n . fst
-- prefix
\n -> (.) ((==) n) fst
-- composition
\n -> ((.) . (==) $ n) fst
-- let's force the application to be of the form (f n (g n))
\n -> ((.) . (==) $ n) (const fst $ n)
-- exploit f <*> g = \n -> f n (g n) -- AKA the S combinator
((.) . (==)) <*> (const fst)
-- remove unneeded parentheses
(.) . (==) <*> const fst
Removing p is left as an exercise.

Why does this point free definition not work in Haskell?

I tried to make the following function definition:
relativelyPrime x y = gcd x y == 1
point-free:
relativelyPrime = (== 1) . gcd
However, this gives me the following error:
Couldn't match type ‘Bool’ with ‘a -> Bool’
Expected type: (a -> a) -> a -> Bool
Actual type: (a -> a) -> Bool
Relevant bindings include
relativelyPrime :: a -> a -> Bool (bound at 1.hs:20:1)
In the first argument of ‘(.)’, namely ‘(== 1)’
In the expression: (== 1) . gcd
In an equation for ‘relativelyPrime’:
relativelyPrime = (== 1) . gcd
I don't quite understand. gcd takes two Ints/Integer, returns one Ints/Integer, then that one Int/Integer is checked for equality to '1'. I don't see where my error is.
It doesn't work because gcd requires two inputs whereas function composition only provides gcd one input. Consider the definition of function composition:
f . g = \x -> f (g x)
Hence, the expression (== 1) . gcd is equivalent to:
\x -> (== 1) (gcd x)
This is not what you want. You want:
\x y -> (== 1) (gcd x y)
You could define a new operator to compose a unary function with a binary function:
f .: g = \x y -> f (g x y)
Then, your expression becomes:
relativelyPrime = (== 1) .: gcd
In fact, the (.:) operator can be defined in terms of function composition:
(.:) = (.) . (.)
It looks kind of like an owl, but they are indeed equivalent. Thus, another way to write the expression:
relativelyPrime = ((== 1) .) . gcd
If you want to understand what's happening then see: What does (f .) . g mean in Haskell?
as you commented on it - if you really want a point-free version you can first use uncurry gcd to transform gcd into a version that accepts a single input (a tuple):
Prelude> :t uncurry gcd
uncurry gcd :: Integral c => (c, c) -> c
then check with (== 1) and finally curry it again for the original signature:
relativeelyPrime = curry ((== 1) . (uncurry gcd))
your version did not work just because gcd produces a function if given only the first argument and this is no legal input for (== 1) which awaits a number.

Point Free problems in Haskell

I am trying to convert the following Haskell code to point free style, to no avail.
bar f g xs = filter f (map g xs )
I'm new to Haskell and any help would be great.
Converting to pointfree style can be done entirely mechanically, though it's hard without being comfortable with the fundamentals of Haskell syntax like left-associative function application and x + y being the same as (+) x y. I will assume you are comfortable with Haskell syntax; if not, I suggest going through the first few chapters of LYAH first.
You need the following combinators, which are in the standard library. I have also given their standard names from combinator calculus.
id :: a -> a -- I
const :: a -> b -> a -- K
(.) :: (b -> c) -> (a -> b) -> (a -> c) -- B
flip :: (a -> b -> c) -> (b -> a -> c) -- C
(<*>) :: (a -> b -> c) -> (a -> b) -> (a -> c) -- S
Work with one parameter at a time. Move parameters on the left to lambdas on the right, e.g.
f x y = Z
becomes
f = \x -> \y -> Z
I like to do this one argument at a time rather than all at once, it just looks cleaner.
Then eliminate the lambda you just created according to the following rules. I will use lowercase letters for literal variables, uppercase letters to denote more complex expressions.
If you have \x -> x, replace with id
If you have \x -> A, where A is any expression in which x does not occur, replace with const A
If you have \x -> A x, where x does not occur in A, replace with A. This is known as "eta contraction".
If you have \x -> A B, then
If x occurs in both A and B, replace with (\x -> A) <*> (\x -> B).
If x occurs in just A, replace with flip (\x -> A) B
If x occurs in just B, replace with A . (\x -> B),
If x does not occur in either A or B, well, there's another rule we should have used already.
And then work inward, eliminating the lambdas that you created. Lets work with this example:
f x y z = foo z (bar x y)
-- Move parameter to lambda:
f x y = \z -> foo z (bar x y)
-- Remember that application is left-associative, so this is the same as
f x y = \z -> (foo z) (bar x y)
-- z appears on the left and not on the right, use flip
f x y = flip (\z -> foo z) (bar x y)
-- Use rule (3)
f x y = flip foo (bar x y)
-- Next parameter
f x = \y -> flip foo (bar x y)
-- Application is left-associative
f x = \y -> (flip foo) (bar x y)
-- y occurs on the right but not the left, use (.)
f x = flip foo . (\y -> bar x y)
-- Use rule 3
f x = flip foo . bar x
-- Next parameter
f = \x -> flip foo . bar x
-- We need to rewrite this operator into normal application style
f = \x -> (.) (flip foo) (bar x)
-- Application is left-associative
f = \x -> ((.) (flip foo)) (bar x)
-- x appears on the right but not the left, use (.)
f = ((.) (flip foo)) . (\x -> bar x)
-- use rule (3)
f = ((.) (flip foo)) . bar
-- Redundant parentheses
f = (.) (flip foo) . bar
There you go, now try it on yours! There is not really any cleverness involved in deciding which rule to use: use any rule that applies and you will make progress.
Both of the existing answers don't really answer your specific question in a way that's elucidating: one is "here are the rules, work it out for yourself" and the other is "here is the answer, no information about how the rules generate it."
The first three steps are really easy and consist in removing a common x from something of the form h x = f (g x) by writing h = f . g. Essentially it's saying "if you can write the thing in the form a $ b $ c $ ... $ y $ z and you want to remove the z, change all the dollars to dots, a . b . c . ... . y:
bar f g xs = filter f (map g xs)
= filter f $ (map g xs)
= filter f $ map g $ xs -- because a $ b $ c == a $ (b $ c).
bar f g = filter f . map g
= (filter f .) (map g)
= (filter f .) $ map $ g
bar f = (filter f .) . map
So this last f is the only tricky part, and it's tricky because the f is not at the "end" of the expression. But looking at it, we see that this is a function section (. map) applied to the rest of the expression:
bar f = (.) (filter f) . map
bar f = (. map) $ (.) $ filter $ f
bar = (. map) . (.) . filter
and that's how you reduce an expression when you don't have complicated things like f x x and the like appearing in it. In general there is a function flip f x y = f y x which "flips arguments"; you can always use that to move the f to the other side. Here we have flip (.) map . (.) . filter if you include the explicit flip call.
I asked lambdabot, a robot who hangs out on various Haskell IRC channels, to automatically work out the point-free equivalent. The command is #pl (pointless).
10:41 <frase> #pl bar f g xs = filter f (map g xs )
10:41 <lambdabot> bar = (. map) . (.) . filter
The point free version of bar is:
bar = (. map) . (.) . filter
This is arguably less comprehensible than the original (non-point-free) code. Use your good judgement when deciding whether to use point-free style on a case-by-case basis.
Finally, if you don't care for IRC there are web-based point-free
converters such as pointfree.io, the pointfree command line program, and other tools.

Project Euler 3 - Haskell

I'm working my way through the Project Euler problems in Haskell. I have got a solution for Problem 3 below, I have tested it on small numbers and it works, however due to the brute force implementation by deriving all the primes numbers first it is exponentially slow for larger numbers.
-- Project Euler 3
module Main
where
import System.IO
import Data.List
main = do
hSetBuffering stdin LineBuffering
putStrLn "This program returns the prime factors of a given integer"
putStrLn "Please enter a number"
nums <- getPrimes
putStrLn "The prime factors are: "
print (sort nums)
getPrimes = do
userNum <- getLine
let n = read userNum :: Int
let xs = [2..n]
return $ getFactors n (primeGen xs)
--primeGen :: (Integral a) => [a] -> [a]
primeGen [] = []
primeGen (x:xs) =
if x >= 2
then x:primeGen (filter (\n->n`mod` x/=0) xs)
else 1:[2]
--getFactors
getFactors :: (Integral a) => a -> [a] -> [a]
getFactors n xs = [ x | x <- xs, n `mod` x == 0]
I have looked at the solution here and can see how it is optimised by the first guard in factor. What I dont understand is this:
primes = 2 : filter ((==1) . length . primeFactors) [3,5..]
Specifically the first argument of filter.
((==1) . length . primeFactors)
As primeFactors is itself a function I don't understand how it is used in this context. Could somebody explain what is happening here please?
If you were to open ghci on the command line and type
Prelude> :t filter
You would get an output of
filter :: (a -> Bool) -> [a] -> [a]
What this means is that filter takes 2 arguments.
(a -> Bool) is a function that takes a single input, and returns a Bool.
[a] is a list of any type, as longs as it is the same type from the first argument.
filter will loop over every element in the list of its second argument, and apply it to the function that is its first argument. If the first argument returns True, it is added to the resulting list.
Again, in ghci, if you were to type
Prelude> :t (((==1) . length . primeFactors))
You should get
(((==1) . length . primeFactors)) :: a -> Bool
(==1) is a partially applied function.
Prelude> :t (==)
(==) :: Eq a => a -> a -> Bool
Prelude> :t (==1)
(==1) :: (Eq a, Num a) => a -> Bool
It only needs to take a single argument instead of two.
Meaning that together, it will take a single argument, and return a Boolean.
The way it works is as follows.
primeFactors will take a single argument, and calculate the results, which is a [Int].
length will take this list, and calculate the length of the list, and return an Int
(==1) will
look to see if the values returned by length is equal to 1.
If the length of the list is 1, that means it is a prime number.
(.) :: (b -> c) -> (a -> b) -> a -> c is the composition function, so
f . g = \x -> f (g x)
We can chain more than two functions together with this operator
f . g . h === \x -> f (g (h x))
This is what is happening in the expression ((==1) . length . primeFactors).
The expression
filter ((==1) . length . primeFactors) [3,5..]
is filtering the list [3, 5..] using the function (==1) . length . primeFactors. This notation is usually called point free, not because it doesn't have . points, but because it doesn't have any explicit arguments (called "points" in some mathematical contexts).
The . is actually a function, and in particular it performs function composition. If you have two functions f and g, then f . g = \x -> f (g x), that's all there is to it! The precedence of this operator lets you chain together many functions quite smoothly, so if you have f . g . h, this is the same as \x -> f (g (h x)). When you have many functions to chain together, the composition operator is very useful.
So in this case, you have the functions (==1), length, and primeFactors being compose together. (==1) is a function through what is called operator sections, meaning that you provide an argument to one side of an operator, and it results in a function that takes one argument and applies it to the other side. Other examples and their equivalent lambda forms are
(+1) => \x -> x + 1
(==1) => \x -> x == 1
(++"world") => \x -> x ++ "world"
("hello"++) => \x -> "hello" ++ x
If you wanted, you could re-write this expression using a lambda:
(==1) . length . primeFactors => (\x0 -> x0 == 1) . length . primeFactors
=> (\x1 -> (\x0 -> x0 == 1) (length (primeFactors x1)))
Or a bit cleaner using the $ operator:
(\x1 -> (\x0 -> x0 == 1) $ length $ primeFactors x1)
But this is still a lot more "wordy" than simply
(==1) . length . primeFactors
One thing to keep in mind is the type signature for .:
(.) :: (b -> c) -> (a -> b) -> a -> c
But I think it looks better with some extra parentheses:
(.) :: (b -> c) -> (a -> b) -> (a -> c)
This makes it more clear that this function takes two other functions and returns a third one. Pay close attention the the order of the type variables in this function. The first argument to . is a function (b -> c), and the second is a function (a -> b). You can think of it as going right to left, rather than the left to right behavior that we're used to in most OOP languages (something like myObj.someProperty.getSomeList().length()). We can get this functionality by defining a new operator that has the reverse order of arguments. If we use the F# convention, our operator is called |>:
(|>) :: (a -> b) -> (b -> c) -> (a -> c)
(|>) = flip (.)
Then we could have written this as
filter (primeFactors |> length |> (==1)) [3, 5..]
And you can think of |> as an arrow "feeding" the result of one function into the next.
This simply means, keep only the odd numbers that have only one prime factor.
In other pseodo-code: filter(x -> length(primeFactors(x)) == 1) for any x in [3,5,..]

Trick for "reusing" arguments in Haskell?

From time to time I stumble over the problem that I want to express "please use the last argument twice", e.g. in order to write pointfree style or to avoid a lambda. E.g.
sqr x = x * x
could be written as
sqr = doubleArgs (*) where
doubleArgs f x = f x x
Or consider this slightly more complicated function (taken from this question):
ins x xs = zipWith (\ a b -> a ++ (x:b)) (inits xs) (tails xs)
I could write this code pointfree if there were a function like this:
ins x = dup (zipWith (\ a b -> a ++ (x:b))) inits tails where
dup f f1 f2 x = f (f1 x) (f2 x)
But as I can't find something like doubleArgs or dup in Hoogle, so I guess that I might miss a trick or idiom here.
From Control.Monad:
join :: (Monad m) -> m (m a) -> m a
join m = m >>= id
instance Monad ((->) r) where
return = const
m >>= f = \x -> f (m x) x
Expanding:
join :: (a -> a -> b) -> (a -> b)
join f = f >>= id
= \x -> id (f x) x
= \x -> f x x
So, yeah, Control.Monad.join.
Oh, and for your pointfree example, have you tried using applicative notation (from Control.Applicative):
ins x = zipWith (\a b -> a ++ (x:b)) <$> inits <*> tails
(I also don't know why people are so fond of a ++ (x:b) instead of a ++ [x] ++ b... it's not faster -- the inliner will take care of it -- and the latter is so much more symmetrical! Oh well)
What you call 'doubleArgs' is more often called dup - it is the W combinator (called warbler in To Mock a Mockingbird) - "the elementary duplicator".
What you call 'dup' is actually the 'starling-prime' combinator.
Haskell has a fairly small "combinator basis" see Data.Function, plus some Applicative and Monadic operations add more "standard" combinators by virtue of the function instances for Applicative and Monad (<*> from Applicative is the S - starling combinator for the functional instance, liftA2 & liftM2 are starling-prime). There doesn't seem to be much enthusiasm in the community for expanding Data.Function, so whilst combinators are good fun, pragmatically I've come to prefer long-hand in situations where a combinator is not directly available.
Here is another solution for the second part of my question: Arrows!
import Control.Arrow
ins x = inits &&& tails >>> second (map (x:)) >>> uncurry (zipWith (++))
The &&& ("fanout") distributes an argument to two functions and returns the pair of the results. >>> ("and then") reverses the function application order, which allows to have a chain of operations from left to right. second works only on the second part of a pair. Of course you need an uncurry at the end to feed the pair in a function expecting two arguments.

Resources